Microcatheter-assisted stenting of the tortuous vertical ductus arteriosus via femoral access in a duct-dependent pulmonary circulation. (15th June 2019) - Haas, N.A.; Fernandez-Rodriguez, S.; Dalla Pozza, R.; Fischer, M.; Ulrich, S.; Jakob, A.; Lehner, A.
Abstract: Background: Stenting of the patent ductus arteriosus (PDA) has been accepted as alternative option to surgical shunting to enable additional pulmonary blood flow or for palliation of patients with a truly duct-dependent pulmonary circulation. The procedure can be challenging given the variable and often tortuous anatomy of the PDA and various technical approaches are reported. Objective: To report an alternative technique to treat tortuous ducts with microcatheter assistance and by transfemoral approach. Methods: We applied this technique of PDA stenting in 5 consecutive patients (4/5 age < 1 week, weight 2, 7–3, 2 kg; 1/5 re-do PDA stenting at 6, 5 month and 5, 9 kg). A soft coronary guidewire was advanced by microcatheter assistance into the branch pulmonary arteries and thereafter replaced by an extrastiff guidewire to enable the placement of long coronary stents. Results: Successful PDA stenting with this stepwise approach and with femoral access only could be achieved in all patients ( n  = 5/5). A single stent was used in 2 patients (one with re-do stenting and previous stents). 3/5 patients had 2 stents implanted by telescopic technique. Stent sizes used were 4, 5 × 15 mm ( n  = 2) and 4, 5 × 18 mm ( n  = 6). No guide wire or stent dislodgement appeared through all procedures with microcatheter assistance. Conclusions: This technique enables PDA stenting via transfemoral approach in complex and tortuous ducts and thereby offers an attractive addition to the interventional management of truly duct-dependent pulmonary circulation.